(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The performance of the journal bearing at the dynamic loading condition under the effect of self-excitation and forced harmonic excitation has been investigated. For this purpose, the conventional form of the Reynolds equation is analyzed numerically using the central finite difference technique with a proper initial and boundary condition. The numerical equations have been written in (FORTRAN-95) language to obtain the results. According to the numerical results obtained, the maximum oil pressure is obtained under the combined effect of forced harmonic vibration and self- excitation is increased by 36.66 percent from those obtained under the self- excitation only.